The Essence of Project Education at the English Lessons in Higher Education Institution - Mustafina, R.F.; Ilina, M.S.; Shcherbakova, I.A. (International Journal of Criminology and Sociology, 2022)
The article reveals the essence of project education in the classroom in the foreign (English) language of students of non-linguistic specialties of the University. Project training is considered by the author as one of the effective teaching methods that allows you to transform academic knowledge into real life experience of students. The author draws attention to the fact that the inclusion of project activities in the educational process of students of the university contributes to the formation and development of information skills that quite effectively fits into the educational process, carried out in the form of a workshop, effective if all the stages of the project activities that necessarily include the presentation. The implementation of project training was carried out on the basis of the University. A sample of the study consisted of 20 first-year students of profile "Lawyer". The study took place in three stages. At the organizational stage, primary diagnostics of the communicative competence development level was carried out through testing and a communicative case. At the second stage, the project activity was carried out within one semester within the framework of the four topics in accordance with the thematic plan of the English language program: “Trip planning”, “The development of the ecological situation”, “Which is better: city or in the countryside?”, “Young people in modern society”. At the third stage, re-diagnosis was carried out by means of testing and a communicative case.